Literature review on advancements in solar absorption refrigeration for sustainable cooling systems - Oubourhim Soukayna; Mmadi Hassane Mohamed; Filali Baba Yousra; Al Mers Ahmed; Kheiri Abdelhamid; Botella Olivier (EPJ Web of Conferences)
Solar-powered absorption refrigeration systems offer a sustainable and energy-efficient alternative to conventional cooling technologies by utilizing solar thermal energy rather than mechanical compression. These systems operate through thermochemical processes, commonly using lithium bromide-water (LiBr-H₂O) or ammonia-water (NH₃-H₂O) as working fluids to generate cooling without reliance on compressors. Ongoing research aims to enhance heat and mass transfer efficiency, optimize thermodynamic cycles, and integrate hybrid configurations to improve overall performance. By combining solar thermal collectors with absorption refrigeration, these systems achieve more effective solar-to-cooling conversion, particularly in regions with abundant sunlight. Advancements in heat exchanger design and working fluid selection contribute to higher reliability and efficiency. Hybrid models, such as the integration of the Organic Rankine Cycle (ORC) with absorption cooling, have been developed to improve energy recovery and stabilize performance under varying solar conditions. Furthermore, advanced control strategies are being implemented to manage energy distribution and ensure continuous operation. These innovations position solar absorption refrigeration as a viable solution for residential, commercial, and industrial cooling applications, promoting sustainability. This paper provides an extensive literature review and discusses recent advancements, highlighting opportunities for future development and potential applications of solar-driven absorption cooling technology.